Research on the influence of loading rate on the dynamic initiation fracture toughness of CMDB propellant - Jian Zheng; Xuan Wu; Zhengwei Sun; Zongtao Guo; Menglong Zhang; Xiong Chen (Scientific Reports)
Abstract In the field of gun launched missile extended range rocket, the propellant grain in the rocket needs to withstand significant launch loads during their firing phase, and also bear the high pressure caused by ignition, and the impact of launch overloads and ignition shocks on the structural integrity of propellants becomes very important. So this work investigated the dynamic initiation fracture toughness of the composite modified double-base (CMDB) propellant by both experiments and numerical simulations. The dynamic mechanical properties test of the cracked straight through flattened Brazilian disc (CSTFBD) specimens were conducted using a modified Split Hopkinson pressure bar (SHPB). By comparing the results of quasi static and dynamic numerical simulations, it was found that dynamic fracture initiation toughness can be determined by time-to-fracture using the quasi-static theory. The numerical simulation results combined with the ZWT constitutive model agree well with the experimental results, indicating that ZWT constitutive model is suitable for numerical simulation calculation of propellant structural integrity under dynamic load, and provides a theoretical basis for propellant structural integrity analysis under dynamic load. During the measurement of the mechanical response, the fracture surfaces of the dynamic test specimens were observed by electron microscopy scanning. Then the evolution of the microstructure synchronously was obtained. The scanning electron microscope (SEM) results revealed that fracture modes and breakage of the ammonium perchlorate (AP) particles in the surface layer played an important role in determining the failure mechanism, which revealed the failure mechanism of the propellant under dynamic load. The result of experimental measurement showed the influence of loading rate on the dynamic fracture initiation toughness of CMDB propellant.